ANALYSIS OF THE FACTORS AFFECTING PROFITABILITY SUSTAINABILITY AND PROFITABILITY: KONYA SUGAR FACTORY WITH A COOPERATIVE OPERATION (Third Sector Social Economic Review, 2017)
Profitability is not taken as basis when vehicles determine their own strategies in changing market conditions. Establishment and establishment of a company. Profitability is the most basic thing that the business continues and the economic activities in the long run are to be carried out. Therefore, one step ahead is based on profitability. In this study, Konya Şeker Fabrikası is examined among the companies registered in Istanbul Chamber of Industry (ISO) and among the first 500 major industrial establishments of Turkey up to 1993-2015. Konya Sugar Factory is one of the first 500 industrial enterprises among the cooperative enterprises and continues its continuity in high sales and profitability items. Therefore, Konya Sugar Factory has been studied in our work. In the literature study we made, a master's thesis titled ""The Effect of Organizational Culture on Business Satisfaction and Its Importance in Business"" was found on the Konya Sugar Factory in 2006. The main purpose of our work is to analyze the factors that affect the profitability in the enterprises using the data of Konya Sugar Factory.
Keywords: Profitability; Cooperative Operation; Konya Sugar Factory; Factors Affecting Profitability